Policy Strategy to Improve The Food Consumption Patterns of The Denpasar City Community that are Diverse, Nutritious, Balanced and Safe - Miki, Ni Wayan (Institute for Research and Community Services Udayana University, 2026)
Food is anything that comes from biological sources, whether processed or not, intended as food and drink for human consumption. The size of a region's food supply is one measure that can reflect the adequacy of food supply in the area concerned, which can influence community consumption patterns as measured by the Expected Food Pattern (PPH) score. In 2024, the PPH score in Denpasar City reached 90.92, indicating that it was in the golden triangle (88-100) but had not yet reached the optimal number (100). The high consumption of rice as the main source of carbohydrates and the lack of diversity in community consumption, resulted in a high dependence on supplies from outside the region or imports. This paper aims to develop policies that can be implemented by the government and relevant stakeholders to increase the use of local non-rice foods for public consumption, especially the people of Denpasar City.